ERA long-term experiment data and analytics (EiA2030/ERA_ltes R-code github) - Steward, Peter Richard; Muller, Lolita; Rosenstock, Todd Stuart; Joshi, Namita; Youngberg, Brayden (2025)
This repository, developed under the CGIAR Excellence in Agronomy (EiA) Initiative, focuses on the analysis of long-term agronomic experiments (LTEs) to better understand the relationships between agricultural practices, climatic factors, and experimental outcomes. The dataset comprises 34,815 individual observations from 181 LTEs, derived from 211 publications across 260 sites in 28 countries (as of 2025-10-01 v0.0.1_alpha). This analysis explores a wide array of agronomic management practices, including crop rotation, fertilization, and intercropping, along with their impacts on productivity, economic performance, and sustainability.